Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su131810018
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Criteria Approach for Arabic Dialect Sentiment Analysis for Online Reviews: Exploiting Optimal Machine Learning Algorithm Selection

Abstract: A sentiment analysis of Arabic texts is an important task in many commercial applications such as Twitter. This study introduces a multi-criteria method to empirically assess and rank classifiers for Arabic sentiment analysis. Prominent machine learning algorithms were deployed to build classification models for Arabic sentiment analysis classifiers. Moreover, an assessment of the top five machine learning classifiers’ performances measures was discussed to rank the performance of the classifier. We integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The result showed that Bidirectional Multi-Layer LSTM has high accuracy. In [ 12 ], author applied SVM, LR, DT, NB, and DL models on the Saudi dialect sentiment Arabic tweets dataset. The result shows that deep learning and SVM classifiers perform best with accuracy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that Bidirectional Multi-Layer LSTM has high accuracy. In [ 12 ], author applied SVM, LR, DT, NB, and DL models on the Saudi dialect sentiment Arabic tweets dataset. The result shows that deep learning and SVM classifiers perform best with accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the research used ML algorithms to predict sentiment analysis and to enhance the sentiment analysis method’s accuracy [ 9 , 10 , 11 ], transit from primarily linear models and evolved until it reached what we see today of the more complex deep neural network. In addition, deep learning (DL) algorithms have been used to extract features with great effectiveness over other ML algorithms such as [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of each classifier was measured by computing the following performance measures: classification accuracy, precision, recall, and F1-score. These measures are commonly used to evaluate the performance of ML models in many research areas, such as rumor detection systems [43,44], clickbait detection [33], as well as in SA [45][46][47].…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…a) Fifth phase: Hybrid supervised classification approach phase: This phase performs two subsections: the first issue is applying ML approach which performs five selected ML classifiers which utilized extensively for ASA: Logistic Regression (LR) [25] [26] [27] [28], Naïve Bayes (NB) [29] [30] [31] [32], K-Nearest Neighbors (KNN) [33] [34] [31] [35], Random Forest (RF) [36] [37] [38] and SVM [33] [39] [40] in addition applying DL approach which performs DL classifier Multi-Layer Perceptron Neural Network (MLP-NN) which applied in [36] [37] for ASA.…”
Section: ) Stop Word Removalmentioning
confidence: 99%